2014
DOI: 10.4103/0976-237x.137959
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the antibacterial activity of simvastatin against periodontal pathogens, Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans: An in vitro study

Abstract: Context and Objective:Statin treatment, apart from its hypolipidemic action has proven its antimicrobial activity by improving the survival rate of patients with severe systemic bacterial infections. Periodontitis is an inflammatory disorder of tooth supporting structures caused by a group of specific microorganisms. The objective of the present study was to determine the antimicrobial activity of pure simvastatin drug against the primary periodontal pathogens.Materials and Methods:Minimum inhibitory concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 38 publications
2
50
0
4
Order By: Relevance
“…These findings support the positive clinical results after local statin application as adjunct to nonsurgical and surgical periodontal procedures . The rationale to use statins in periodontal therapy is based on their antimicrobial, anti‐inflammatory and bone‐promoting properties . In particular, statins are shown to be effective against A. actinomycetemcomitans and Porphyromonas gingivalis , 2 of the major species of bacteria implicated in periodontitis pathogenesis.…”
Section: Discussionsupporting
confidence: 64%
“…These findings support the positive clinical results after local statin application as adjunct to nonsurgical and surgical periodontal procedures . The rationale to use statins in periodontal therapy is based on their antimicrobial, anti‐inflammatory and bone‐promoting properties . In particular, statins are shown to be effective against A. actinomycetemcomitans and Porphyromonas gingivalis , 2 of the major species of bacteria implicated in periodontitis pathogenesis.…”
Section: Discussionsupporting
confidence: 64%
“…These could be attributed to the added values of SMV used in the present study for both groups with its known effect on fibroblastic proliferation . SMV was found to inhibit tissue degrading enzymes like MMPs and have anti‐microbial properties . Many studies reported positive results during the regeneration of periodontal bone defects after the application of SMV with methylcellulose gel .…”
Section: Discussionmentioning
confidence: 66%
“…The use of EDTA gel at neutral pH (24%) as a root surface conditioner was carried out for smear layer removal, exposing dentine collagen fibers and increasing the diameter of the dentinal tubules which could enhance migration and attachment of fibroblast and could allow more SMV local adsorption to the root surface improving its availability . Many studies reported that EDTA root surface etching could enhance drug availability over the root surfaces or in the GCF like chlorhexidine and doxycycline . Filter paper was used for GCF sampling as it is the easiest and a more precise method for GCF collection …”
Section: Discussionmentioning
confidence: 99%
“…2 Porphyromonas gingivalis, Tannerella forsythia, and Aggregatibacter actinomycetemcomitans are major periodontitis-causing pathogens. 3,4 Lipopolysaccharide (LPS) from gram-negative bacteria such as P. gingivalis has been identified as the main factor inducing periodontitis. 5 Stimulation of gingival fibroblasts by LPS induces the activation of nuclear factor kappa B (NF-kB) and mitogen-activated protein kinase (MAPK) pathways, which finally results in the release of cytokines, such as tumour necrosis factor alpha (TNF-a), interleukin (IL)-6, and IL-8.…”
Section: Introductionmentioning
confidence: 99%